Penerapan Sanksi Pidana Peraturan Daerah Kota Kupang Nomor 10 Tahun 2007 Tentang Retribusi Izin Usaha Pemeliharaan Ternak Terhadap Peternakan - Bani, Putri Paskalia Pati; Pello, Jimmy; Leo, Rudepel Petrus (Law Faculty, Nusa Cendana University, 2025)
The main problems of this research are (1) Has the criminal sanction in Local Regulation No. 10/2007 on Retribution for Livestock Keeping Business License in Kupang City been applied against livestock keepers in the jurisdiction of Kupang City District Court? and (2) What are the factors inhibiting the application of criminal sanctions in Local Regulation No. 10/2007 on Retribution for Livestock Keeping Business License in Kupang City? This type of research is empirical juridical research, namely research with a juridical approach that examines primary legal materials, tertiary legal materials and secondary legal materials and examines existing data in the field while still paying attention to legal theories, principles and rules. The data collection techniques used are interviews, questionnaires and document studies. The results of this study show: (1) The application of criminal sanctions in Regional Regulation No. 10 of 2007 concerning Retribution for Livestock Maintenance Business License, namely: (a) Forms of Criminal Sanctions in Local Regulation Number 7 Year 2007, (b) Application of Criminal Sanctions in Local Regulation Number 10 Year 2007, (2) Factors inhibiting the application of criminal sanctions in Local Regulation Number 10 Year 2007 on Retribution of Livestock Maintenance Business License in Kupang City (a) Low Public Legal Awareness. (b) Weak Supervision and Socialization. (c) The absence of a special budget for enforcement of local regulations, (d) the existence of social tolerance for violations.